PENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALY, REPETITION (AIR) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVA SDN 032 KUALU - Dina Putri Hasyim; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the lack of IPS student learning outcomes, it is seen in the he problem in this research is the lack of IPS student learning outcomes, it is seen in the value of students who reached the KKM (Minimum Criteria for completeness), only 14 (40%) of 35 students. While KKM specified school is 70, meaning many students who have not reached the KKM is 21 people (60%). Based on these problems need to be done to implement the action research Auditory Learning Model, Intellectualy, Repetition (AIR). In the first cycle of the first meeting of the percentage of activity the teachers gained 83.3% in both categories, at the second meeting of the percentage increased to 87.5% in both categories. At the first meeting of the second cycle the percentage increased to 91.6% with very good category, at the second meeting of the percentage increased to 95.8% with very good category. Activities of students has increased, in the first cycle of the first meeting of the percentage of the student activity gained 79.1% in both categories, at the second meeting of the percentage increased to 83.3% in both categories. At the first meeting of the second cycle the percentage increased to 87.5% with very good category, and at the second meeting of the percentage increased to 91.6% with very good category.Average students achievement in before application is 64 increased to 74,3 in the first cycle, and increasing again to 91,2 in the second cycle. While the classical completeness in the first cycle and the second cycle is reached. This means that the Auditory, Intellectualy, Repetition (AIR) implementation can increase students achievement at IPS in fourth graderes SD Negeri 032 Kualu.Key Words: Model Auditory Intellectualy Repetition (AIR), IPS achievement